The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1981
DOI: 10.1128/jb.147.3.851-859.1981
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline resistance transposon Tn1721: recA-dependent gene amplification and expression of tetracycline resistance

Abstract: The 7.1-megadalton transposon Tn1721 codes for inducible tetracycline resistance (Tcr). The transposable element consists of a "minor transposon" (3.6 megadaltons) encoding functions required for transposition and a "tet region" (3.5 megadaltons) encoding resistance. Multiple tandem repeats of the tet region can be generated by recA-dependent gene amplification. This feature of Tn1721 has been used to analyze the relationship between gene dosage and Tcr. Derivatives of plasmid R388:Tn1721 containing from one t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 35 publications
(76 reference statements)
0
21
0
Order By: Relevance
“…The tandem duplication of genes provides a mechanism for amplifying gene expression. Analysis of bacteria selected for increased antibiotic resistance has shown that they often contain tandem duplicated copies of an antibiotic resistance gene that is present in low copy number in unselected bacteria (Wiebauer et al, 1981). By analogy with bacteria, the tandem repetition of the MATE genes could provide a mechanism for increasing the resistance of plants to toxic compounds in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…The tandem duplication of genes provides a mechanism for amplifying gene expression. Analysis of bacteria selected for increased antibiotic resistance has shown that they often contain tandem duplicated copies of an antibiotic resistance gene that is present in low copy number in unselected bacteria (Wiebauer et al, 1981). By analogy with bacteria, the tandem repetition of the MATE genes could provide a mechanism for increasing the resistance of plants to toxic compounds in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…Tnl 724 is a derivative of Tn) 721 with a chloramphenicol resistance determinant encoded on a 3.3-kb HindIII fragment (from R plasmid Sa; 9, 28), which was ligated into the single HindIII site of Tn)722 (24). Tn1725 was derived from Tnl724 by the recA-dependent elimination of the tet region (29), resulting in a modified Tn1722 that carries a chloramphenicol resistance marker (P. Rogowsky, unpublished data).…”
Section: Methodsmentioning
confidence: 99%
“…The majority of clones thus selected contained insertions of Tnl725 into pJOE398. Plasmids from each clone were separately isolated by the rapid isolation method (29) and transformed into strain HB11. The number of chloramphenicol-resistant transformants ranged between 0 and 200.…”
Section: Transformation and In Vitro Generation Of Deletionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In TB90, mutagenesis can be induced with the addition of L-(+)-arabinose (Sigma; Methods S1; Table S6). The TB90 strain lacks the recA gene, to reduce recombination and gene loss among duplicate TEM-1 copies as well as to minimize the incidence of higher order amplifications (Reams et al 2010), which have already been studied (Wiebauer et al 1981;Goldberg and Mekalanos 1986;Reams et al 2012). For all E. coli cultures, we used LB medium (Becton-Dickinson).…”
Section: Bacterial Strains and Mediummentioning
confidence: 99%